(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper discusses different classes of aggregation operators and their applications to Interval Vague Set (IVS) decision making problems.Correlation coefficient for interval vague sets is proposed and utilized in Multiple Attribute Group Decision Making (MAGDM) problems. Ordered Weighted Geometric (OWG) operators are used for the MAGDM models proposed for IVSs and the proposed correlation coefficient is used for ranking alternatives. A data mining algorithm is also utilized for reducing the number of alternatives for the final decision making process. Numerical illustrations are provided for MAGDM models for interval vague sets.